Impact of Pulmonary Hypertension on Posttransplant Survival of Patients With Pulmonary Fibrosis at High Altitude: A Prospective Cohort Study - Fabio Varón-Vega; Luis J. Telléz; Eduardo Tuta-Quintero; Adriana Rincón; Diana Casas; Camilo Rodriguez; David Mendoza; Luis Fernando Giraldo-Cadavid (Canadian Respiratory Journal)
Conclusion: Survival at 1 and 5 years was lower in patients with PH. However, no significant differences in survival were observed based on sex, mPAP, age, or BMI. Statistically significant improvements in FVC, FEV1, 6MWT, and SGRQ total scores were observed both before and after LT, continuing through 1 year of follow-up. The 6MWT and SGRQ showed MCID both prior to surgery and during follow-up at 6 and 12 months, in both PH and non-PH patients.